Comparison of step-by-step kinematics of elite sprinters' unresisted and resisted 10-m sprints measured with Optojump or Musclelab - van den Tillaar, R. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to compare step-by-step kinematics of unresisted and resisted 10-m sprints measured with the Optojump or Musclelab on elite sprinters. Six subjects (age 30.0 ± 5.1 years, body mass 76.3 ± 5.3 kg, body height 1.79 ± 0.09 m, and 100-m personal best 10.51 ± 0.3 s) performed 2 unresisted and 2 sets of 2 resisted (10 and 20% of body mass) 30-m sprints in random order (6 sprints in total) in 1 session in which kinematics of the first 10 m were measured with the Optojump and Musclelab. The main finding was that there were no significant differences between the measurements made with the Optojump and Musclelab systems. In addition, it was possible to discriminate most kinematic variables per step of the first 10 m when different loads (10 and 20% of body mass) had to be pulled during the 30-m sprints. The variations in sprint times associated with changes in the resistance provided by the dynaSpeed were mainly caused by a decrease in step length as the resistance increased. It was concluded that the 2 systems are valid and could help coaches, researchers, and athletes by providing more detailed information about possible changes to kinematics during training and sprinting with different resistances.